A Review on Basic Income: A Radical Proposal for a Free Society and a Sane Economy by Philippe Van Parijs and Yannick Vanderborght - Calsamiglia, Caterina; Flamand, Sabine (Journal of Economic Literature, 2019)
In order to clarify the potential impact of a basic income, we argue that any discussion on whether to adopt a basic income policy should be framed within the greater context of the transfer system as a whole. In particular, such discussion should consider separately the issues of (i) the desired income distribution to be achieved and (ii) the most efficient way of achieving it through a transfer system. Further, we stress the importance of the non-take-up phenomenon in current transfer systems and discuss the potential necessity of a basic income policy in the age of automation. (JEL D31, I32, I38)